CH_BUNDESRAT /bj/de/home/publiservice/publikationen/beschwerdeentscheide/2025-02-12.html vom 12. Februar 2025 - Bundesrat (2025)
Beschwerdesache A. gegen Eidgenössisches Departement für auswärtige Angelegenheiten. Entscheid